Effect of Elagolix Exposure on Clinical Efficacy End Points in Phase III Trials in Women With Endometriosis‐Associated Pain: An Application of Markov Model - Insa Winzenborg; Akshanth R. Polepally; Ahmed Nader; Nael M. Mostafa; Peter Noertersheuser; Juki Ng (Wiley, 2020)
Elagolix is an oral gonadotropin‐releasing hormone antagonist approved by the US Food and Drug Administration (FDA) for the management of moderate‐to‐severe pain associated with endometriosis and in combination with estradiol/norethindrone acetate approved for the management of heavy menstrual bleeding associated with uterine leiomyomas (fibroids) in premenopausal women. The objective of this work was to characterize the relationships between elagolix exposures and clinical efficacy response rates for dysmenorrhea (DYS) and nonmenstrual pelvic pain (NMPP) in premenopausal women enrolled in the pivotal phase III studies with moderate‐to‐severe pain associated with endometriosis. Relationships between elagolix average concentrations (Cavg) and efficacy responses (DYS and NMPP) were characterized using a nonlinear mixed‐effects discrete‐time first order Markov modeling approach. Only age was statistically significant for NMPP but not considered clinically relevant. This work indicates that the selection of elagolix dose is not determined based on tested patient demographics, baseline, or endometriosis disease severity measures in covariate analysis. In other words, the work suggests no preference of one regimen over the other to treat endometriosis‐associated pain (DYS or NMPP) for any patient subpopulation based on tested covariate groups.